Distal arterial occlusions in patients with mild strokes-: is endovascular therapy superior to thrombolysis alone? - Nagel, Simon; Pfaff, Johannes; Herweh, Christian; Schieber, Simon; Mundiyanapurath, Sibu; Schönenberger, Silvia; Seker, Fatih; Möhlenbruch, Markus Alfred; Ringleb, Peter A. (Journal of stroke and cerebrovascular diseases, 2020)
Background and Purpose - Safety and efficacy of endovascular thrombectomy (EVT) in patients with mild stroke syndromes is unclear, especially in distal vessel occlusions. - Methods - We analysed in our stroke database (HeiReKa) between 2002 and April 2019 safety and efficacy of EVT compared to intravenous thrombolysis (IVT) in patients with occlusions distal to the M1 segment of the middle cerebral artery and the top of the basilar artery who presented with a National Institute of Health Stroke Scale (NIHSS) below 6. Excellent (good) outcome was defined as modified rankin scale (mRS) 0-1 (0-2) or return to baseline mRS (good) after 3 months. Safety endpoints were mortality after 3 months and intracranial hemorrhage according to the Heidelberg Bleeding Classification (HBC). - Results - Of 4167 patients 94 met the inclusion criteria. Sixty-four patients were allocated to the IVT group and 30 to the EVT group of which 15 also received IVT; three patients (4.6%) in the IVT group received rescue EVT. Baseline characteristics did not differ but more M2 occlusions were found in the EVT group (93.3% vs. 64.1%, p=0.02). Intracranial bleeding occurred more often in EVT patients (HBC class 2: 13.3% vs. 1.6%, p=0.01). Excellent and good outcome were not significantly different (75% vs. 70%, p=0.65 and 87.5% vs. 73.3%, p=0.14). Mortality was significantly lower in IVT patients (1.6% vs. 13.3%, p=0.04). - Conclusion - Rates of excellent and good outcome after IVT or EVT were almost similar, but safety parameters were increased after EVT. EVT may be considered in selected patients after careful risk/benefit analysis.
Gesehen am 15.07.2020